Three-Dimensional Laplace Adomian Decomposition Method and Singular Pseudoparabolic Equations - Hassan Eltayeb; Diaa Eldin Elgezouli; Adem Kilicman; Imed Bachar (Journal of Function Spaces)
In this work, the solution of the linear, nonlinear, and coupled system fractional singular two-dimensional pseudoparabolic equation is examined by using a three-dimensional Laplace Adomian decomposition method (3-DLADM). Analysis of the method is discussed, and some demonstrative examples are mentioned to confirm the power and accuracy of the recommended method, and numerical analysis is applied to sketch the exact and approximate solution.